The Seven Dwarfs and the Age of the Mandarins: Australian Government Administration in the Post-War Reconstruction Era - Furphy, Samuel (ANU Press, 2015)
In the history and folklore of Australia's Commonwealth Public Service, the idea of the 'Seven Dwarfs' has been remarkably persistent. Originally a witty epithet applied to a powerful group of senior public servants, the term has come to represent the professionalisation of Australian government administration during the Second World War and post-war reconstruction era, and into the following two decades of expansion. This was a period when, for the first time, talented university graduates entered the public service, rose to senior levels, and exerted great influence over the affairs of the Commonwealth. With the secure tenure of being permanent heads of departments, they defined the age of the public service mandarin. This book explores the lives and influence of the Seven Dwarfs and their colleagues, bringing together the leading researchers on post-war Australian administration. Featuring four thematic chapters and ten biographical portraits, it offers a fascinating insight into the workings of the Commonwealth Public Service during a critical period in its history.